2020
DOI: 10.1002/acr.24440
|View full text |Cite
|
Sign up to set email alerts
|

Positive Psychological Factors and Impairment in Rheumatic and Musculoskeletal Disease: Do Psychopathology and Sleep Quality Explain the Linkage?

Abstract: Objective. Little is known about potential mechanisms of action linking protective positive psychological variables and functional disability in patients with rheumatic and musculoskeletal disease. The present study was undertaken to examine symptoms of psychopathology, including stress, depression, anxiety, and sleep quality, as serial mediators of the association between gratitude, self-compassion, self-forgiveness, and functional impairment. Methods. We assessed risk and protective factors for functional di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…6. Applying positive psychology approaches [gratitude, self-compassion, and self-forgiveness, cognitive restructuring] alongside efforts to foster empowerment [61,64].…”
Section: Journal Of Aging Research and Healthcarementioning
confidence: 99%
“…6. Applying positive psychology approaches [gratitude, self-compassion, and self-forgiveness, cognitive restructuring] alongside efforts to foster empowerment [61,64].…”
Section: Journal Of Aging Research and Healthcarementioning
confidence: 99%
“…Many meta-analyses have shown that short and long sleep durations are associated with all-cause mortality [2][3][4]. Moreover, sleep may improve musculoskeletal disease at the psychological level [5][6][7][8]. It has also been reported that sleep duration is associated with obesity and diabetes [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Rheumatic diseases are generally characterized by a chronic course that both affects patients' physical, mental, and social function and significantly impacts their caregivers and family members, resulting in low health-related quality of life (QoL) as well as psychological problems ( 1 , 2 ). For this reason, over the last decade, health related QoL has become an evolving field of research; and data from the literature increasingly highlight the relationship between disease activity/damage and the ability to work and psychological wellbeing.…”
mentioning
confidence: 99%